The Distribution of K. pneumoniae in Different Specimen Sources and Its Antibiotic Resistance Trends in Sichuan, China From 2017 to 2020 - Zhang, Jie; Li, Dan; Huang, Xiangning; Long, Shanshan; Yu, Hua (Frontiers in Medicine, 2022)
Objective: We aim to analyze the distribution of Klebsiella pneumoniae in different specimen sources and its antibiotic resistance trends from the Antimicrobial Resistant Investigation Network of Sichuan Province (ARINSP) between 2017 and 2020. Methods: According to the monitoring scheme, each participating hospital identified the bacteria and performed antimicrobial susceptibility tests using approved procedures. The data of non-repetitive isolates collected from outpatients and inpatients were submitted to ARINSP. The WHONET 5.6 software was used to analyze the results according to the Clinical and Laboratory Standards Institute (CLSI). Results: Between 2017 and 2020, 833,408 non-repetitive clinical isolates of bacteria were isolated in total. The bacterial strains isolated from sputum and broncho-alveolar lavage accounted for 48.7%, 56.4%, 49.2%, and 43.7% from 2017 to 2020 respectively, among all sources. The number of Klebsiella pneumoniae isolates from sputum and broncho-alveolar lavage increased from 18,809 in 2018, 19,742 in 2019, to 19,376 in 2020, playing a predominant role among all specimens. Meropenem-resistant K. pneumoniae occurrences (5.7% in 2017, 7.3% in 2018, 8.0% in 2019, and 7.5% in 2020) remained highest among carbapenems, and increased slightly over time. The resistance rate to tigecycline remained lowest, and declined from 2.4% in 2017, to 0.4% in 2018, and from 0.7% in 2019, to 0.6% in 2020. Conclusion: The overall resistance rates of Klebsiella pneumoniae to carbapenems increased in Sichuan Province, giving a significant challenge to control K. pneumoniae related infections. Tigecycline has retained activity to against K. pneumoniae. Ongoing surveillance is essential. It can help for implementing intervention programs to reduce the occurrence of antimicrobial resistance and to provide with a rational use of antimicrobials.